Relationship between passion, resilience and performance in triathlon (Research, Society and Development, 2020)
This research aimed to analyze the relationship between passion, resilience, and performance in triathletes. The sample was composed of 78 male athletes ( age = 36.97 ± 10.29 years), participating in two national-level competitions which took place in 2018. Instruments used were an identification sheet, the Passion Scale (PS), and the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). Athletes’ performance was obtained by their total time in the race. Data analysis was performed through R software (version 3.6.3), using the Shapiro-Wilk, Wilcoxon, Mann-Whitney’s U, Spearman correlation coefficient and Binomial Logistic Regression tests, with significance level of p